Preferred Clearing and Post-Trade Costs - Alizadeh, Behnoud; Zoican, Marius (The Review of Asset Pricing Studies, 2026)
We study fee competition between an incumbent and entrant central counterparty (CCP) under two regimes: interoperability (trades clear at each party’s own CCP) and preferred clearing (trades clear at the incumbent unless both counterparties choose otherwise). Preferred clearing creates network effects that force the entrant to undercut aggressively, while the incumbent sustains higher fees. Fee spreads, average trading costs, and industry profits increase under preferred clearing. However, interoperability is costly because linked CCPs must post collateral against cross-CCP exposure. Interoperability improves welfare when link costs are either low or high enough that the incumbent drops fees to reduce clearing fragmentation. (JEL G11, G12, G14)